COGNITIVE BIASES IN FOREIGN EXCHANGE TRADING DECISIONS IN IRAQ - Dr. Basman Kamel Jawad (Scholars Digest Publishing, 2024)
This research aims to analyze the pulses of cognitive biases in the decisions of traders in the currency market in Iraq to determine their impact on foreign exchange traders and their ability to avoid risks. Cognitive and perceptual biases are more likely among investors who have low education and little experience. Experience and knowledge grow and develop with the development of the country’s economy and markets. Finance and Monetary As is known, the Iraqi economy has not witnessed development due to the historical stages that it has passed. Therefore, a large group of biases was chosen that represented the independent variables, while the traders’ decisions represented the dependent variables. This research relied on the analytical research method, relying on a sample of bank managers. The business reached 220 financial and administrative managers, and the statistical program SPSS was relied upon in order to reach accurate results. The research concluded with a set of conclusions, the most important of which is that all biases affect the decisions of foreign currency traders in Iraq. This confirms the lack of knowledge and scientific experience among the public of foreign currency traders and confirms the importance of keeping up with international studies and specialized courses that contribute to raising the scientific and technical level of advanced cadres. In the banking sector, the study concluded with a set of recommendations, the most important of which is that the state should have a role in spreading awareness in this field by encouraging researchers to conduct scientific research in this field and providing seminars and courses that increase the knowledge and ability of traders to avoid risks, hedge, and achieve profits.
Keywords: cognitive biases, foreign exchange, currency market, foreign exchange traders.